Caribbean Business Clinic: Model for the Economic Reactivation of the Huetar Caribbean Region - Binns Hernández, Henry (2025)
The joint and committed alliance of three sectors: academia, the private sector and the public sector have generated a successful multidimensional conceptual work model for the regional economic development of the Caribbean region of Costa Rica called the “Triple Helix”. In this model, the prominent role of the Costa Rican public university has been fundamental not only because it provides innovation and creativity to respond to the demands of society in terms of knowledge, but also because it plays a mediating role in taking and integrating business production with government regulatory demands and directing them towards local development and rural territories. This form of cooperation has been achieved in the Huetar Caribbean Region of Costa Rica through the academic platform of university extension and social action. Based on the diagnoses and analyses of macro and micro environmental factors in the province of Limón, Costa Rica, through the extension project “Caribbean Business Clinic” registered at the Costa Rican Institute of Technology, it is clear that there is a need to improve administrative and operational functions, strengthening the management capacities of micro, small and medium-sized companies of commercial, tourist, logistics and agricultural products and services in the region; this is due to the lack of resources and knowledge for the proper development and economic and business growth of businesses. The objective is to strengthen the management capacities of MSMEs in the Huetar Caribe Region of Costa Rica through the triple helix model by integrating companies in formal and informal conditions and attached to institutions and organizations from both the public and private sectors, having as a main strategy the use of tools such as training workshops, advice, monitoring and project formulation.